Penerapan Metode Waterfall Pada Sistem Informasi Persediaan PT. Hansae Indonesia Sukses Berbasis Dekstop - Norma Yunita; Aisyah Aisyah; Siti Marlina (Universitas Bina Sarana Informatika, 2023)
PT. Hansae Indonesia Sukses is a company engaged in garment. Currently, the process of controlling office stationery inventory at PT Hansae Indonesia Sukses has not been computerized because it still uses the Ms Excel program. The business process that is being carried out is less than optimal starting from the incoming, outgoing and reporting goods so that the length of the process of searching for data and inaccurate reports is not enough. Thus in this study, the authors made a computerized system for recording office stationery supplies in the process of incoming goods to reports using the desktop-based PHP programming language. This system was developed with a design that is not too complicated to make it easier for the user in the process of managing incoming goods, outgoing goods and reports. From the manufacture of this system is expected to optimize the performance of the admin compared to the previous manual system